Gaseous and Electrochemical Hydrogen Storage Properties of Mg-Based Thin Films - Xin, Gongbiao; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2016)
In this thesis, the author introduces the preparation of a series of Mg-based thin films with different structures by magnetron sputtering, and the systematical investigation of their gaseous and electrochemical hydrogen storage properties under mild conditions. The promising applications of Mg-based thin films in smart windows, hydrogen sensors and Ni-MH batteries are also reviewed. The research work presented in this thesis offers significant perspectives on the research of Mg-based hydrogen storage materials, especially the Mg-based films. Moreover, the unique experimental procedures and methods (including the electric resistance, optical transmittance and electrochemical methods) used in this thesis can also provide valuable reference for the researchers in the field of Mg-based hydrogen storage films.
Introduction -- The Effects of Ti, Al Interlayers on the Hydrogen Storage Properties of 100nm Mg-Pd Films under Mild Conditions -- The Effects of Structure Tailoring on the Gaseous and Electrochemical Hydrogen Storage Properties of 500nm Mg-Pd Films under Mild Conditions -- The Effects of Morphologies on the Gaseous and Electrochemical Hydrogen Storage Properties of 200nm Mg-Pd Films -- The Effects of Different Mg-Ti Atom Ratios on the Electrochemical Hydrogen Storage Properties of Mgxti1-X-Pd Films -- Conclusions and Outlooks.
Keywords: Inorganic chemistry; Surfaces (Technology).; Thin films; Electrochemistry; Nanotechnology; Inorganic Chemistry; Surfaces, Interfaces and Thin Film; Electrochemistry; Nanotechnology